PENGARUH DISIPLIN KERJA DAN PROMOSI JABATAN TERHADAP KINERJA KARYAWAN PT PERMODALAN MADANI PERSERO - Elyza Deswita; Ahmad Rivai; Martin, Martin (Jurnal Mahkota Bisnis (Makbis), 2024)
This study aims to gain an in-depth understanding and provide empirical evidence regarding the influence of work discipline and job promotion on job satisfaction and their impact on employee performance. The approach used in this research is a quantitative approach, with statistical analysis and regression analysis as the methods employed. The study is designed as a survey researchs with a sample size of 100 employees from PT Permodalan Nasional Madani (Persero) in Medan. The results of the study indicate that work discipline partially affects the performance of employees at PT Permodalan Madani Persero. Job promotion also affects employee performance, and work discipline and job promotion simultaneously influence the performance of employees at PT Permodalan Madani Persero